From Clappique to Sganarelle: Fluttering with Malraux and Gary - Roumette, Julien (Literatūra, 2022)
Romain Gary is not close to André Malraux only by his political and war time commitments. They also share a form of creative fantasy that shakes up literary genres, embodied by the character of Clappique, in La Condition Humaine. He serves as a model for the recurring figure of the Baron in Romain Gary’s novels, through different incarnations from Le Grand Vestaire to Les Couleurs du jour and Clair de femme. Fanciful and comical portraits, these caricatural characters appear as a buffoonish recourse in the face of history. Gary will push this salutary counterpoint very far, gradually releasing the comic force of his fantasy, while Malraux will not resist giving this endearing double a last lap in his Antimémoires. Seeing the writer as Clappique makes it possible to show the fruitfulness and the constancy of this “wacky” (« farfelue ») dimension, which is part of the companionship between the two writers.
Keywords: Burlesque; Farfelu; 20th century french novel; comedy; idealism; farcical mythomania